Synthesis, spectroscopic and Biological Studies of New Metallic Chelates Derived from (E)-N'-(3,5-dimethoxybenzylidene)isonicotinohydrazide (Journal of the College of Basic Education, 2025)
Coordination compounds of Schiff base-based isonicotinic acid of transition metals has formed complexes of cobalt(II), nickel(II), copper(II) and zinc(II) utilizing new bi dentate ligands;HL namely as: and HL namely: (E)-N'-(3,5-dimethoxybenzylidene)isonicotinohydrazide. The two new ligands were synthesized by the condensation reaction of isoniazid with ethanolic solution of 3,5-dimethoxybenzaldehyde. The metal complexes were prepared and isolated in their solid state after adjusting the reaction conditions such as time reaction, mole ratios (M: L), and pH of the reaction medium. The synthesized isoniazid Schiff base and its metal complexes were fully characterized based on elemental analyses (C.H.N.S), metal content via FAAS, IR, UV-visible-NIR, NMR spectra, molar conductivity, and magnetic susceptibility measurements. The results revealed an octahedral geometry around cobalt (II), nickel (II), copper (II) ions in [M (L) Cl2 (H2O)2].2H2O formula. According to result of biological activity, free ligands had little to no effect, while the majority of metal complexes, especially those of cobalt, demonstrated strong antibacterial and antifungal activity. The results of biological activity showed that cobalt (II) and copper (II) complexes were most effective than the free ligand, L and its nickel (II) complex against all microorganisms tested. The suggestion for these results has been assigning to the effect of less polarity and formation the coordination and covalence bonding in the metal complexes rather than the free ligand, beside the penetration of metal complexes the lipophilic layer of bacteria and fungi may be ascribed to chelation effect.